Description Analysis of Semester Implementation Plan and Teaching Materials for Tolaki Language: A Preliminary Study of Tolaki Language Teaching Materials Development - Arliwan, Disa; Mayuni, Ilza; Kamal, Muhamad (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Semester implementation plans and teaching materials are important documents in supporting the learning process. This study aims to describe the semester implementation plan and teaching materials for Tolaki language courses currently used in the Indonesian Language and Literature Education study program at Lakidende University. Data were obtained from document studies, interviews and observations. The results of research related to semester implementation plans include aspects of learning objectives, material focus, methods, and evaluation, while the results of teaching material research include interest in teaching materials, validity and reliability of materials, attractiveness, benefits of materials and students’ views on teaching materials, ease of use of teaching materials, and flexibility of teaching materials. The results of this study will be a reference for developing semester implementation plans and teaching materials that refer to the needs of lecturers and students as users. For this reason, this research is very important to do to find out the needs of students and lecturers that are relevant to the curriculum and teaching materials.